2022
DOI: 10.24843/bulvet.2023.v01.i01.p03
|View full text |Cite
|
Sign up to set email alerts
|

Prevalensi Infeksi Cacing Nematoda Gastrointestinal pada Ayam Petelur di Desa Peninjoan, Kecamatan Tembuku, Kabupaten Bangli, Bali

Abstract: Nematoda termasuk kelompok parasit cacing yang penting menginfeksi unggas sehubungan dengan banyaknya spesies dan kerusakan yang ditimbulkan.  Cacing nematoda yang umum menginfeksi saluran pencernaan ayam diantaranya adalah Capilaria spp, Tetrameres spp, Aquaria spp, Ascaridia galli, Strongyloides avium, Trichostrongylus sp dan Heterakis gallinarum.  Faktor risiko yang berpengaruh terhadap kejadian infeksi parasit dipengaruhi oleh; hospes, parasit dan lingkungan.  Faktor hospes yang paling umum berpengaruh, te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
2
0
0
Order By: Relevance
“…and facilitate direct transmission to the chickens. This observation is consistent with Belo et al (2023), who found that temperature and humidity factors in the cage influence the development of eggs to the infective stage, thereby increasing the occurrence of infections. Transmission can occur directly through contaminated food and water.…”
Section: ■ Results and Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…and facilitate direct transmission to the chickens. This observation is consistent with Belo et al (2023), who found that temperature and humidity factors in the cage influence the development of eggs to the infective stage, thereby increasing the occurrence of infections. Transmission can occur directly through contaminated food and water.…”
Section: ■ Results and Discussionsupporting
confidence: 92%
“…The trichurid eggs had thick walls, were oval-shaped, and featured bipolar plugs at both ends (Figure 1). This finding aligns with those reported by Belo et al (2023). Trichurid eggs measure 45-50 µm in length and 22-25 µm in width, with slightly protruding bipolar plugs, a thick shell with wrinkled surface, and granular, non-segmented contents (Kusuma et al 2021).…”
Section: ■ Results and Discussionsupporting
confidence: 92%